PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DIMASA PANDEMI COVID-19 PADA PT LONSUM BULUKUMBA - Iftita Islamia Fatima; Ramli, Anwar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the Physical Work Environment and Non-Physical Work Environment partially or simultaneously on Employee Productivity at PT. Lonsum Bulukumba. The population in this study were permanent employees (MRP) totaling 70 people who were also the sample in this study. Collecting data using the questionnaire method (questionnaire). While the data analysis technique used is Multiple Linear Regression Analysis using two statistical test methods, namely Simultaneous Test (F-test) and Partial Test (t-test) using Statistical Product and Service Solution (SPSS). Based on the analysis results indicate that the Physical Work Environment and Non-Physical Work Environment have a simultaneous effect on Employee Productivity, which means a pleasant work environment can increase employee productivity. The Physical Work Environment has a partial effect on Employee Productivity, meaning that the conditions of a comfortable work space and work facilities and infrastructure that support work can increase Employee Productivity at work. Non-Physical Work Environment has a partial effect on Employee Productivity, meaning that conducive working conditions and harmonious employee relations can increase employee productivity at work.